Small but smart: international shared virtual class link-up during the pandemic 2020-2021 - third-level students in Ireland and Israel - Tal Yaar-Waisel; Gerry O’Reilly (European Journal of Geography)
This paper explores the experiences of a cooperative class link-up between geography students and teachers in Ireland and Israel in 2021 during the Coronavirus lockdowns, and hence the use of virtual education.  There was a followed-up class in 2022. The aim was experimental T&L, enhanced by cooperative approaches, with the objectives of getting students from different cultures to interact, discover their shared geographies, and reflect on their self-perception of their countries and preconceptions of other countries and people. Implicit in the PBL was to gain greater awareness of cultural and critical geopolitics. Another aim was for the two lecturers managing the course, to share their pedagogies and experiences. This paper is not simply exploring the ‘teacher telling or guiding the trainee teachers’ what to do but calling on lecturers and trainers to reflect on their own attitudes and perceptions in delivering quality Geographical Education.  Student group work entailed a series of activities: (i) Icebreaker: Hello – Ireland and Israel. (ii) Model lesson: joint preparation of a geography class on Ireland and Israel. (iii) Fieldwork: development of a joint virtual trip for students to Israel and to Ireland emphasizing the places selected by each subgroup; and (iv) an evaluation of the experiences of the class link-up. The main communication devices used were Zoom for joint class sessions, while students selected WhatsApp for small mixed group work. Despite some challenges for students and teachers, in their evaluations, they all agreed that the experience was positive for them.